Evaluation of Dried Poultry Manure in Layer Rations - Peethambran P A (Department of Poultry Science, College of Veterinary and Animal Sciences, 1978)
Forty single comb White Leghorn pullets aged 25 weeks were divided in to four groups of 10 birds each and the groups were on diets containing O (control), 10, 15 and 20 per cent dried poultry manure for 168 days. The entire period of study was divided in to six periods of 28 days each. The results of this study revealed that the incorporation of dried poultry manure at 15 per cent level was better than 0, 10 and 20 per cent levels in terms of hen-day egg production, feed efficiency and egg weight. The feed consumption, pattern of body weight maintenance and livability of birds were not effected by the different dietary treatments. However, the feed efficiency was found to significantly better at 15 per cent level of incorporation than that at 20 per cent level. Egg weight was significantly decreased at 10 per cent level than 15 and 20 per cent levels of DPM in the diet. Per cent shell, per cent albumen and per cent yolk showed no appreciable different attributable to the inclusion of DPM at different levels in layer rations. Based on the overall performance of the birds fed 15 per cent dried poultry manure in the diet it was concluded that this level excelled the 0, 10 and 20 per cent level of DPM incorporation and proved to be more beneficial and economic.